Curbing Our Enthusiasm: An Analysis of the Check-In/Check-Out Literature Using the Council for Exceptional Children's Evidence-Based Practice Standards. (May 2017) - Mitchell, Barbara S.; Adamson, Reesha; McKenna, John W.
Check-in/Check-out (CICO) is an intervention designed to improve behavioral outcomes for students identified as at-risk for school failure. Core principles of the intervention include clearly defined behavioral expectations and rules, precorrections for meeting behavioral expectations, high rates of feedback and reinforcement for demonstration of desired behavior, use of data to monitor outcomes, and a system for school-to- home communication. The purpose of this investigation was to use the 2014 Council for Exceptional Children's quality indicators and standards for establishing evidence-based practices in special education to review the existing research for CICO. Implications regarding the use of different sets of quality indicators to evaluate extant research are provided, and recommendations for future research are discussed.